Cooperatives: Collaboration in communication - Tsegaye, Mebratu (Technical Centre for Agricultural and Rural Cooperation, 2010)
A broad partnership of individuals, businesses, NGOs, and government departments is supporting an ICT cooperative to improve rural connectivity in the Butajira area of Ethiopia.